Polycaprolactone as biomaterial for bone scaffolds: Review of literature - Ruby Dwivedi; Sumit Kumar; Rahul Pandey; Aman Mahajan; Deepti Nandana; Dhirendra S. Katti; Divya Mehrotra (Elsevier, 2020)
Bone tissue engineering using polymer based scaffolds have been studied a lot in last decades. Considering the qualities of all the polymers desired to be used as scaffolds, Polycaprolactone (PCL) polyester apart from being biocompatible and biodegradable qualifies to an appreciable level due its easy availability, cost efficacy and suitability for modification. Its adjustable physio-chemical state, biological properties and mechanical strength renders it to withstand physical, chemical and mechanical, insults without significant loss of its properties. This review aims to critically analyse the efficacy of PCL as a biomaterial for bone scaffolds.